The last plumassier: storying dead birds, gender and Paraffection at Maison Lemarié. (January 2018) - Pacault, Marine; Patchett, Merle
Founded in 1875, Maison Lemarié is one of the last remaining plumassiers (feather-makers) anywhere in the world. In highly concentrated and minutely detailed work, the artisans at Lemarié painstakingly treat, dye and apply fragile feathers to haute couture garments. Mindful of preserving these rarefied skills, Chanel (a global fashion empire) purchased the workshop in 1997 as part of 'Paraffection'. Paraffection, which roughly translates to 'for the love of it', is a Chanel subsidiary company established to preserve and promote the heritage, craft and manufacturing skills of highly specialized fashion ateliers. By enacting a visit to Maison Lemarié, this article demonstrates how its heritage and skills are embodied not only in the artisans working there but also in the feathered remains used and housed in the workshop. Unravelling the stories held in human and avian bodies, we suggest, enables a series of broader geographical reflections on skill, gender and Paraffection.